Review of the Renal Artery Anatomy: In Chronic Kidney Disease and Healthy Individuals - Aktaş, Gülsüm Derya; Ünver Doğan, Nadire; Çelik, Gülperi; Koplay, Mustafa; Fazlıoğulları, Zeliha; Altındaş, İbrahim; Karabulut, Ahmet Kağan (European Journal of Therapeutics, 2023)
Objective: The purpose of this study was to evaluate renal arteries and aorta anatomy in patients with chronic kidney disease (CKD) and compare them with a control group. Methods: Computed tomography images of 800 individuals (551 of that were with CKD and 249 of them were completely healthy in terms of urinary system) were evaluated retrospectively. Age range of the individuals 19 - 91 years (mean 61.15 ± 12.58). The differences between the renal arteries diameters, diameters of aorta, courses of the renal arteries, their separation levels from the aorta was investigated between the control group and patients with CKD. Results: Diameters of aorta and renal arteries are larger in CKD patients than healthy individuals and there was a negative correlation between the diameters of aorta with glomerular filtration rate. No statistically significant difference was observed between CKD patients and healthy individuals in terms of renal artery course. No statistically significant difference was detected between CKD patients and healthy individuals in terms of the branching level of the renal arteries from the aorta. Conclusion: Our study is one of the first studies which these measurements were made in individuals with CKD, according to the available literature. This study is important in that it reveals that the diameters of the renal arteries are statistically significantly larger in patients with CKD than in healthy individuals. These data may be important for the surgeons in interventional applications